Sorption Properties of Cation-Exchanged Heulandite - M.W. Kasture; S.S. Tamhankar; V.V. Joshi; A.L. Choudhari; V.P. Shiralkar (Adsorption Science & Technology, 1997)
Samples collected from the Aurangabad District, Maharashtra, India were characterized by XRD, IR, TGA and DTA methods, and by chemical analysis, as calcium-rich heulandite. Samples of potassium heulandite (K-Heu) and hydrogen heulandite (H-Heu) were prepared by ion exchange, their thermal stabilities being confirmed by XRD, IR, TGA and DTA methods. Water sorption studies were carried out at five different temperatures on the parent material (P-Heu) and on K-Heu and H-Heu. Different sorption models were tested on the data obtained and the corresponding results are reported.